THE EFFECT OF THE TOTAL CREDIT RECEIVABLE UPON THE REVENUE OF CREDIT SERVICE AT KPRI-KPDK IN SUKABUMI - Nani Pujiastuti (STIE Binaniaga, 2017)
”The influence of the number of credit receivable against the revenue of the credits services at KPRI-KPDK in Sukabumi”. The Credit receivable at KPRI-KPDK in Sukabumi is an indication that an increasing does not mean positive one because it showed that the volume activities services has been arisen however the increasing receivable having a risk, therefore KPRI-KPDK in Sukabumi has a lot of things to reconsider in determining the procedure of the credit given. This research has identified how the influence of a credit against the revenue of the services at KPRI-KPDK in Sukabumi The data used is the primary data which is the data refers to the Report of the Annual Members Meeting (RAT) at KPRI-KPDK in Sukabumi. The research data refers to: financial report which is the balance sheets for five years from 2008 up to 2012 related to the end year of the responsibility report of KPRI-KPDK in Sukabumi and this report is expected to figure out the cooperation unit accordingly. This research has been indicating the numbers of receivable credits as KPRI-KPDK has been increased during 2008-2009, although in 2010, it was decreased but the following years of 2011-2012 it has increased The revenue of the credit service at KPRI-KPDK in Sukabumi has been increasing each year, though it is not quite significant in percentage but it is quite stable ever since The influence of the amount of the total loan against the revenue of the credit service has been positive which r = 0.840 indicating that the variable x has been affecting significantly against the the number of the receivable credit variables y or the revenue of the credit service which is 6%. The Data of the calculation analysis has obtained y regression equation = 39.852.081,767 + 0,123 (X). It means that every 1.00 of the number of receivable credit will affect the revenue of credit services amounting to Rp 0.123,00. Thus writer has been able to make a conclusion that the total amount of the credit receivable has been affecting the revenue of the credit services at KPRI-KPDK in Sukabumi accordingly.Keywords: credit receivable and revenue services credit